Gaya Kepemimpinan Perempuan dalam Peningkatan Kinerja Pegawai (Studi Kasus Pemimpin Daerah Kabupaten Tanggamus) - Halida Novera; Yulianto Yulianto; Simon Sumanjoyo Hutagalung (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2020)
Leadership style is important in an organization, if a leader can adapt his leadership style to the existing situations and conditions, it can affect the performance of his subordinates. In Tanggamus Regency currently led by a woman leader, namely Dewi Handajani, different from previous periods in this period the first time Tanggamus Regency was led by a woman. Therefore, this study aims to determine the leadership style of Tanggamus Regency regional leaders and whether this leadership style affects the performance of employees in Tanggamus Regency. The method used in this research is descriptive research method with a qualitative approach, data collection is done using interview and documentation techniques. The results showed that the leadership style used by the local leaders of Tanggamus Regency, namely the feminine leadership style tends to be transformational and the style applied is able to influence the improvement of employee performance in Tanggamus Regency.